Water supply and distribution systems - Savić, Dragan A.; Banyard, John K. (Emerald Publishing Limited, 2024)
Water Supply and Distribution Systems, Second edition is a comprehensive introduction to the topic of how water is delivered to homes and businesses throughout the world. It covers fundamental concepts and exploring the latest ideas of good practice. Water supply and distribution systems are a key element of essential urban infrastructure. Water utilities worldwide are embarking on a process of 'digitalisation', which promises to bring benefits to the industry, but this is fraught with uncertainty, hype, barriers to innovation and requires an organisational culture change. Water industry professionals have to address, not only, classic design and management problems but also, increasingly, environmental and sustainability requirements and concerns. Drawing together information that is currently scattered across several sources, this book aims to alleviate the concerns engineers have with these issues. With chapters written by academics and practitioners this book covers modelling planning operational and management issues leakage management optimal design asset planning and management a new chapter on smart new water systems. Water Supply and Distribution Systems is a key text for early-stage practitioners, students in training to become water industry practitioners, and a useful reference book for practising engineers, particularly to provide up-to-date information on practices in today's increasingly complex water industry.